An annealing method for quartz glass of optical elements, product and application
Patent Information
- Application Number
- CN202611203430.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-08-10
AI Technical Summary
[0005]针对现有技术的缺陷或改进需求,本申请提供了一种用于光学元件的石英玻璃的退火方法、产品及应用,旨在解决石英玻璃在退火过程中,因羟基浓度差异导致内部粘度不均引起热应力,无法满足对应力双折射要求较高的光学应用需求的技术问题
1、通过采用侧面和顶部分区独立控温方式,在退火降温阶段使石英玻璃顶部区域先于侧面周向区域进入降温阶段,并在降温过程中保持顶部区域温度比侧面周向区域低预设温差,主动补偿了羟基浓度梯度引起的粘度差异,避免了在降温过程中因粘度不均产生新的热应力。实验数据表明,边缘应力双折射值从传统退火工艺的7.21nm/cm降至0.66nm/cm,中心应力双折射值从0.70nm/cm降至0.23nm/cm,显著提升了光学元件用石英玻璃的应力双折射性能。
Smart Images

Figure CN122685303B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of quartz glass heat treatment technology, and more specifically, relates to an annealing method, product and application of quartz glass for optical components. Background Technology
[0002] Quartz glass is widely used in optical components due to its excellent optical properties and thermal stability. For high-precision optical applications, the uniformity and stress birefringence of quartz glass are required to be high. Any residual stress will cause birefringence, resulting in changes in the polarization state and wavefront distortion of light transmitted through the glass, which seriously affects the quality of optical imaging.
[0003] Currently, in the two-step process for preparing synthetic quartz glass, hydroxyl groups diffuse from the center to the edge during the dehydroxylation sintering process, resulting in a radial gradient distribution of hydroxyl concentration that gradually decreases from the center to the edge in the final product. Within the quartz glass, hydroxyl groups break Si-O-Si bridges through Si-OH bonds, forming network breakpoints. Higher hydroxyl concentrations lead to poorer network continuity and lower glass viscosity. Therefore, quartz glass with a hydroxyl concentration gradient exhibits significant internal viscosity differences at the same temperature.
[0004] Annealing is a crucial process for eliminating internal stress in quartz glass, typically involving two steps: high-temperature holding to relax the structure and precise control of the cooling rate. Current annealing processes primarily avoid temperature gradients caused by size effects by controlling the cooling rate, generally keeping it at extremely low levels (e.g., 0.25℃ / h). However, this process neglects the influence of hydroxyl concentration gradients on internal viscosity distribution. Even with extremely low cooling rates, viscosity inhomogeneity due to differences in hydroxyl concentration still leads to varying relaxation rates in different regions, generating thermal stress during annealing. This fails to meet the demands of optical applications requiring high stress birefringence. Summary of the Invention
[0005] In view of the deficiencies or improvement needs of the prior art, this application provides an annealing method, product and application of quartz glass for optical components, which aims to solve the technical problem that the uneven internal viscosity caused by the difference in hydroxyl concentration during the annealing process of quartz glass causes thermal stress, which cannot meet the requirements of optical applications with high stress birefringence.
[0006] In a first aspect, this application provides an annealing method for quartz glass used in optical components, which includes the following steps: The cylindrical quartz glass to be annealed is placed in the annealing equipment, and the required temperature difference T is calculated based on the radial hydroxyl concentration difference and dimensional parameters of the quartz glass. The quartz glass is annealed independently in two separate temperature zones: the circumferential side region and the top region. The circumferential side region and the top region are heated to the same temperature simultaneously. Then, the top region begins to cool down before the circumferential side region. During the cooling process, the temperature of the top region is kept lower than the temperature of the circumferential side region by a temperature difference T, thereby completing the annealing process of the quartz glass.
[0007] As a further preferred embodiment, the temperature difference T is determined using the following formula: T = T1 + T2; T1 = a × △OH; T2=b×(R 2 / 4c)×d; In the formula, T is the temperature difference, T1 is the temperature value that needs to be compensated for the difference in hydroxyl groups, T2 is the temperature value that needs to be compensated for the difference in size, a is the hydroxyl group influence base, ΔOH is the absolute value of the difference in radial hydroxyl concentration in the quartz glass, b is a constant, R is the radius of the quartz glass, c is the thermal diffusivity of the quartz glass at the center of the first stage cooling range in the circumferential region of the side, and d is the cooling rate in the first stage of the circumferential region of the side.
[0008] As a further preferred embodiment, the annealing process of the circumferential region of the quartz glass side is as follows: first, heat to a first preset temperature t1 and hold for a first preset time s1, then cool to a second preset temperature t2 at a first preset cooling rate v1 and hold for a second preset time s2, and finally cool to a third preset temperature t3 at a second preset cooling rate v2, wherein the second preset cooling rate v2 is greater than the first preset cooling rate v1.
[0009] As a further preferred embodiment, the annealing process of the top region of the quartz glass is as follows: simultaneously heating the circumferential region of the side of the quartz glass to the first preset temperature t1 and holding it at that temperature for a third preset time s3, then cooling it down to the fourth preset temperature t4 at the first preset cooling rate v1 and holding it at that temperature for a fourth preset time s4, and finally cooling it down to the third preset temperature t3 at the second preset cooling rate v2.
[0010] As a further preferred embodiment, the first preset temperature t1 is 1260℃~1280℃, the first preset time s1 is 20h~50h, the first preset cooling rate v1 is 1℃ / h~10℃ / h, the second preset temperature t2 is 1050℃~1000℃, the second preset time s2 is 20h~50h, the second preset cooling rate v2 is 5℃ / h~30℃ / h, and the third preset temperature t3 is 500℃.
[0011] As a further preferred embodiment, the first preset time s1 and the third preset time s3 satisfy the following conditions: .
[0012] As a further preferred embodiment, the second preset time s2 and the fourth preset time s4 satisfy the following condition: .
[0013] As a further preferred embodiment, the second preset temperature t2 and the fourth preset temperature t4 satisfy the following conditions: t2-t4=T.
[0014] As a further preferred option, thermal insulation measures are employed to reduce heat transfer between the circumferential side region and the top region.
[0015] Secondly, this application provides a quartz glass for optical components, which is annealed using the above-mentioned annealing method.
[0016] Thirdly, this application provides an application of quartz glass in optical components, wherein the quartz glass is annealed using the above-mentioned annealing method.
[0017] In summary, compared with the prior art, the technical solutions conceived in this application have the following main technical advantages: 1. By employing independent temperature control for the sides and top, the top region of the quartz glass enters the cooling stage before the circumferential side regions during the annealing cooling process. During cooling, the temperature of the top region is maintained at a preset lower temperature difference than the circumferential side regions. This actively compensates for the viscosity difference caused by the hydroxyl concentration gradient, avoiding new thermal stresses generated due to viscosity inhomogeneity during cooling. Experimental data show that the edge stress birefringence value decreases from 7.21 nm / cm in the traditional annealing process to 0.66 nm / cm, and the center stress birefringence value decreases from 0.70 nm / cm to 0.23 nm / cm, significantly improving the stress birefringence performance of quartz glass for optical components.
[0018] 2. By establishing the temperature difference calculation formula T=T1+T2, where T1=a×△OH quantitatively calculates the influence of the hydroxyl concentration gradient, and T2=b×(R² / 4c)×d quantitatively calculates the influence of the size effect, precise control of annealing process parameters is achieved. This application comprehensively considers multiple factors such as hydroxyl concentration differences, quartz glass diameter, thermal diffusivity, and cooling rate, providing a general annealing process design method for quartz glasses of different specifications and hydroxyl concentration gradients. This improves the controllability and repeatability of the annealing process and can guide the precision annealing of this type of quartz ingot.
[0019] 3. Thermal insulation measures were adopted between the circumferential side area and the top area to reduce heat transfer between the two heating zones, thereby improving the independence and accuracy of zoned temperature control. Experimental data show that after adding thermal insulation measures, the edge stress birefringence value further decreased from 2.25 nm / cm to 0.66 nm / cm, an improvement of 70.7%, proving the role of thermal insulation measures in improving the annealing effect. Attached Figure Description
[0020] Figure 1 This is a flowchart of an annealing method for quartz glass used in optical components, provided in an embodiment of this application. Figure 2 This is an annealing process curve diagram of the top region and the side circumferential region provided in the embodiments of this application; Figure 3 yes Figure 2 A magnified view of a section at point A in the middle; Figure 4 This is a schematic diagram of the annealing equipment involved in the comparison. Figure 5 This is a schematic diagram of the annealing equipment with independent temperature control in the partitions involved in Embodiment 1 of this application; Figure 6 This is a schematic diagram of the partitioned independent temperature-controlled annealing equipment with added heat insulation structure involved in Embodiment 2 of this application; Figure 7 This is a graph showing the test results of the stress birefringence value of the material after comparative annealing. Figure 8 This is a graph showing the test results of the stress birefringence value of the material after annealing treatment in Example 1; Figure 9 This is a graph showing the test results of the stress birefringence value of the material after annealing treatment in Example 2; Figure 10 This is a graph showing the test results of the stress birefringence value of the material after annealing treatment in Example 3; Figure 11 This is a graph showing the test results of the stress birefringence value of the material after annealing treatment in Example 4.
[0021] In all the accompanying drawings, the same reference numerals are used to denote the same elements or structures, wherein: 1-Side heating structure, 2-Lower heating structure, 3-Platform, 4-Material, 5-Thermocouple, 6-Upper heating structure, 7-Insulation structure. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0023] This application provides an annealing method for synthetic quartz ingots with uneven radial hydroxyl distribution. Specifically, a master rod with hydroxyl distribution prepared by a two-step method is processed into a cylindrical synthetic quartz ingot. The quartz ingot is then placed in a zoned independent temperature-controlled annealing device. The side and upper heating zones are then activated simultaneously and heated to a preset temperature and held at that temperature. The upper heating zone is cooled first, followed by the side heating zone, to ensure that the cooling rates of the two zones are consistent. Finally, by controlling the cooling time, the temperature difference between the upper zone and the side is ensured to reach the required value. After being held at a certain low temperature, the ingot is simultaneously cooled with the furnace to obtain a quartz ingot with the required stress.
[0024] Specifically, such as Figure 1 As shown, the annealing method specifically includes the following steps: S1. Place the cylindrical quartz glass to be annealed in the annealing equipment and calculate the required temperature difference T based on the radial hydroxyl concentration difference and dimensional parameters of the quartz glass. S2. The side circumferential region and the top region of the quartz glass are annealed independently using a zoned independent temperature control method. The side circumferential region and the top region are heated to the same temperature at the same time, and the top region starts to cool down before the side circumferential region. During the cooling process, the temperature of the top region is kept lower than the temperature of the side circumferential region by the temperature difference T, thereby completing the annealing process of the quartz glass.
[0025] By adopting a zoned independent temperature control method, the temperature difference between the center and the edge of the quartz glass is actively maintained during the annealing and cooling stage, which specifically compensates for the viscosity difference caused by the hydroxyl concentration gradient and avoids the generation of new thermal stress due to uneven viscosity during the cooling process.
[0026] Specifically, the temperature difference T is determined using the following formula: T = T1 + T2; T1 = a × △OH; T2=b×(R 2 / 4c)×d; In the formula, T is the temperature difference, T1 is the temperature value that needs to be compensated for the difference in hydroxyl groups, and T2 is the temperature value that needs to be compensated for the difference in size; a is the hydroxyl group influence base, taken as 0.1℃ / ppm; △OH is the absolute value of the radial hydroxyl group concentration difference of the quartz glass (unit: ppm); b is a constant, taken as 1; R is the radius of the quartz glass (unit: m), and c is the thermal diffusivity of the quartz glass (unit: m). 2 / s, specifically refers to the thermal diffusivity at the center of the cooling range during the first stage of annealing of the circumferential side region), and d is the cooling rate (unit K / s) of the first stage of cooling of the circumferential side region.
[0027] The above calculation formula takes into account the influence of both hydroxyl concentration gradient and size effect on temperature difference, providing a general annealing process design method for quartz glass of different specifications and hydroxyl concentration gradients.
[0028] In a preferred embodiment, such as Figure 2 and Figure 3 As shown, the annealing process for the circumferential region of the quartz glass side is as follows: first, heating to a first preset temperature t1 and holding at that temperature for a first preset time s1; then cooling to a second preset temperature t2 at a first preset cooling rate v1 and holding at that temperature for a second preset time s2; finally, cooling to a third preset temperature t3 at a second preset cooling rate v2, wherein the second preset cooling rate v2 is greater than the first preset cooling rate v1. This staged cooling process uses a slower cooling rate in the critical temperature range to ensure sufficient structural relaxation, and a faster cooling rate in the low-temperature range to improve production efficiency.
[0029] In a preferred embodiment, such as Figure 2 and Figure 3 As shown, the annealing process for the top region of the quartz glass is as follows: It is heated simultaneously with the circumferential region of the side surface to a first preset temperature t1 and held at that temperature for a third preset time s3. Then, it is cooled to a fourth preset temperature t4 at a first preset cooling rate v1 and held at that temperature for a fourth preset time s4. Finally, it is cooled to a third preset temperature t3 at a second preset cooling rate v2. This staged cooling process ensures both effective annealing and improved efficiency. The top region and the circumferential side surface use the same starting and ending temperatures, and temperature difference control is achieved through the difference in holding time and intermediate temperatures. The initial heating rates for the circumferential side surface and the top region of the quartz glass can be set as needed, typically between 5℃ / h and 50℃ / h.
[0030] Specifically, the first preset time s1 and the third preset time s3 satisfy the following conditions: .
[0031] By controlling the insulation time of the side circumferential area to be longer than that of the top area, the top area enters the cooling stage before the side circumferential area, thereby establishing and maintaining a temperature difference during the cooling process.
[0032] Furthermore, the second preset time s2 and the fourth preset time s4 satisfy the following conditions: .
[0033] By adjusting the holding time and cooling rate using the above method, the required temperature difference can be maintained between the circumferential and top regions of the quartz ingot from the first preset temperature to the second preset temperature. Controlling the temperature difference between the circumferential and top regions compensates for the temperature differences caused by hydroxyl group variations and cooling, ensuring that any region in the radial direction is at the same viscosity within this temperature range, thus avoiding the generation of new thermal stress due to viscosity differences. Furthermore, the second preset temperature t2 and the fourth preset temperature t4 satisfy the following conditions: t2-t4=T.
[0034] Maintain the set temperature difference throughout the critical cooling phase to ensure that the viscosity difference caused by the hydroxyl concentration gradient is fully compensated.
[0035] In a preferred embodiment, the first preset temperature t1 is 1260℃~1280℃, the first preset time s1 is 20h~50h, the first preset cooling rate v1 is 1℃ / h~10℃ / h, the second preset temperature t2 is 1050℃~1000℃, the second preset time s2 is 20h~50h, the second preset cooling rate v2 is 5℃ / h~30℃ / h, and the third preset temperature t3 is 500℃. The above parameter design comprehensively considers the radial hydroxyl concentration distribution, the size of the quartz ingot, and the temperature difference between zones, thus improving the optical uniformity and stress birefringence of the quartz ingot.
[0036] In a preferred embodiment, thermal insulation measures are employed to reduce heat transfer between the circumferential side regions and the top region. These measures improve the independence and precision of zoned temperature control, reduce heat interference between the two heating zones, and enable more accurate temperature difference control. Experimental data show that, with the addition of thermal insulation, the edge stress birefringence value can be further reduced to 29% of its original value.
[0037] Specifically, heat insulation is achieved by setting up a heat insulation structure 7, the main purpose of which is to separate the top heating and the side heating. The heat insulation structure 7 can be, for example, a heat insulation ring, located above the quartz glass at a distance of 5mm to 15mm, preferably 10mm. The outer diameter of the heat insulation ring is smaller than the diameter of the quartz glass and is concentric with the quartz glass. The heat insulation ring is made of a good heat-insulating ceramic fiber board from an oxidation furnace. Of course, other heat insulation structures and materials can also be used, as long as the heat insulation purpose is achieved; these will not be elaborated upon here.
[0038] This application also provides a quartz glass for optical components, which is annealed using the above method. This quartz glass has excellent optical uniformity and low stress birefringence, meeting the requirements of high-precision optical applications.
[0039] This application also provides an application of the above-mentioned quartz glass as an optical element material. This quartz glass can be used to manufacture high-precision optical elements, such as high-precision exposure etching equipment and high-precision deep space exploration equipment, which have high requirements for stress birefringence.
[0040] The following are specific examples: Comparative Example The two-step synthetic quartz ingots were processed into cylindrical material 4 with a diameter of 420 mm and a thickness of 100 mm, and its radial hydroxyl concentration distribution was 20~70 ppm. Then, it was placed in... Figure 4 The annealing apparatus shown is prepared for annealing on its platform 3. The apparatus includes a side heating structure 1 and a bottom heating structure 2. The side heating structure 1 heats the sides of the material 4, and the bottom heating structure 2 heats the bottom of the material 4. The annealing apparatus also includes a thermocouple 5 for measuring the temperature at the center of the furnace.
[0041] The side heating structure 1 and the lower heating structure 2 are turned on simultaneously with the same power. First, the temperature is heated to 1280℃ at a rate of 50℃ / h and held for 30 hours. Then, the temperature is reduced to 1000℃ at a rate of 1℃ / h and held at 1000℃ for 30 hours. Finally, the temperature is reduced to 500℃ at a rate of 5℃ / h and the heating power is turned off at the same time.
[0042] The stress birefringence value of material 4 was measured, and the results were: edge stress birefringence value 7.21 nm / cm, center stress birefringence value 0.70 nm / cm. The stress test specifically divides the test area into multiple small grids (generally 1 mm × 1 mm), and each small grid has a stress value. The stress test result is the maximum value among all small grids in the area, for example, within a circle D300 (the same applies below).
[0043] Example 1 The two-step synthetic quartz ingots were processed into cylindrical material 4 with a diameter of 420 mm and a thickness of 100 mm. The radial hydroxyl concentration distribution was 20~70 ppm (ΔOH=50 ppm). Then, it was placed in... Figure 5The annealing process is prepared on the stage 3 of the partitioned independent temperature-controlled annealing equipment shown. This annealing equipment includes a side heating structure 1 and an upper heating structure 6. The side heating structure 1 heats the sides (circumferential direction) of the material 4, and the upper heating structure 6 heats the top of the material 4. Compared to existing annealing equipment, this equipment adds an upper heating structure and eliminates the lower heating structure. Thermocouples 5 are installed on the center surfaces of the sides and top of the material 4 to monitor the temperature of the sides and top, respectively. The monitored temperatures are transmitted to an external temperature controller. The external temperature controller calculates the temperature difference based on the monitored temperature data and preset temperature data, and transmits this difference to a power controller. The power controller controls the heating power of the corresponding heating structures (side heating structure 1 and upper heating structure 6) based on the temperature difference to ensure that the corresponding areas reach the preset temperature. Through independent monitoring and control of the side and top temperatures, the set temperature difference between them is maintained. The side heating structure 1 and the upper heating structure 6 can be commonly used heating structures in existing technology, as long as they can achieve heating; details are not provided here.
[0044] Based on the difference in hydroxyl concentration ΔOH = 50 ppm and the quartz glass dimensional parameters, the required temperature difference to be compensated is calculated as follows: T1 = 0.1 × 50 = 5℃, T2 ≈ 5℃ (c = 6.12 × 10⁻⁶). -7 m 2 / s, which is the thermal diffusivity of the quartz ingot in the first stage of cooling range of 1280℃~1000℃ in the circumferential region on the side (center value 1140℃), d=v1=1℃ / h), and the comprehensive calculation T≈10℃.
[0045] The annealing process of the side circumferential area (side heating structure 1) is as follows: heat to the first preset temperature t1=1280℃ at a rate of 50℃ / h, hold for the first preset time s1=30 hours, then cool to the second preset temperature t2=1000℃ at a first preset cooling rate v1=1℃ / h, hold for the second preset time s2=28 hours, and finally cool to the third preset temperature t3=500℃ at a second preset cooling rate v2=5℃ / h, and then turn off the heating power.
[0046] The annealing process for the top region (upper heating structure 6) is as follows: simultaneously heated to a first preset temperature t1 = 1280℃ along with the side circumferential region, and held at that temperature for a third preset time s3 = = 30 = 20 hours (s3) s1, the top area enters the cooling stage before the side circumferential area), then cools down at the first preset cooling rate v1=1℃ / h to the fourth preset temperature t4=t2-T=1000℃-10℃=990℃, and holds for the fourth preset time s4=30 hours. Finally, cool down at the second preset cooling rate v2=5℃ / h to the third preset temperature t3=500℃, and then turn off the heating power.
[0047] The side circumferential region and the top region are heated to the first preset temperature simultaneously. During the annealing and cooling process from 1280℃ to 1000℃ (the first stage cooling range), the top region is always kept 10℃ lower than the side circumferential region by a specified temperature difference.
[0048] Table 1 Annealing process parameters for the side circumferential region and top region
[0049] The stress birefringence values of material 4 were measured, and the results were: edge stress birefringence value 2.25 nm / cm, center stress birefringence value 0.25 nm / cm.
[0050] Example 2 The two-step synthetic quartz ingots were processed into cylindrical material 4 with a diameter of 420 mm and a thickness of 100 mm. The radial hydroxyl concentration distribution was 20~70 ppm (ΔOH=50 ppm). Then, it was placed in... Figure 6 The annealing process is prepared on the stage 3 of the partitioned independent temperature control annealing equipment shown. The annealing equipment has a heat insulation structure 7 between the side heating structure 1 and the upper heating structure 6. The rest of the structure is the same as in Embodiment 1. By setting the heat insulation structure, the heat transfer between the two heating zones is reduced, thereby improving the independence and accuracy of partitioned temperature control.
[0051] The temperature difference calculation is the same as in Example 1, T≈10℃. The annealing process parameters are the same as in Example 1. The side circumferential area and the top area are heated to the first preset temperature at the same time. During the annealing and cooling process from 1280℃ to 1000℃ (the first stage cooling range), the top center area is always kept 10℃ lower than the side circumferential area.
[0052] The stress birefringence values of material 4 were measured, and the results were: edge stress birefringence value 0.66 nm / cm, and center stress birefringence value 0.23 nm / cm.
[0053] Example 3 Based on Example 2, the first preset cooling rate v1 was changed to 3℃ / h, while other parameters remained unchanged. The stress birefringence value of material 4 was measured, and the results were: edge stress birefringence value 1.39nm / cm, center stress birefringence value 0.26nm / cm.
[0054] Example 4 Based on Example 2, the first preset time for heat preservation of the side hot zone was changed to s1=20 hours, and the third preset time for heat preservation of the center hot zone was changed to s3=10 hours, while other parameters remained unchanged. The stress birefringence value of material 4 was measured, and the results were: edge stress birefringence value 1.69nm / cm, center stress birefringence value 0.31nm / cm.
[0055] Table 2 Test results of stress birefringence values
[0056] The test results for the comparative examples and Examples 1-4 are shown in Table 1. Figures 7-11 As can be seen from the comparison of the comparative examples with Examples 1 and 2, the method of using independent temperature control in zones and maintaining a specific temperature difference T between the top region and the side circumferential region during the annealing cooling stage can effectively eliminate the thermal stress caused by the uneven internal viscosity due to the hydroxyl concentration gradient.
[0057] Compared to the comparative example, in Example 1, the edge D400 stress birefringence value decreased from 7.21 nm / cm to 2.25 nm / cm, a reduction of 68.8%, and the center D100 stress birefringence value decreased from 0.70 nm / cm to 0.25 nm / cm, a reduction of 64.3%.
[0058] Example 2 adds heat insulation measures based on Example 1, further reducing the edge D400 stress birefringence value to 0.66 nm / cm, a reduction of 90.8% compared to the comparative example, and reducing the center D100 stress birefringence value to 0.23 nm / cm, a reduction of 67.1% compared to the comparative example.
[0059] Compared to Example 1, Example 2 showed that the edge D400 stress birefringence value decreased from 2.25 nm / cm to 0.66 nm / cm, an improvement of 70.7%, demonstrating the effect of heat insulation measures on improving the annealing effect.
[0060] By comparing Examples 3 and 4 with the comparative examples, it can also be seen that the annealing process of this application can effectively eliminate the thermal stress caused by the uneven internal viscosity due to the hydroxyl concentration gradient.
[0061] It is understood that the heating method of the annealing equipment is not limited to graphite resistance heating, but can also be metal resistance heating, silicon carbide rod heating, or silicon molybdenum rod heating, or other heating methods commonly used in the art. The annealing equipment can be a vacuum annealing furnace or an atmosphere-protected annealing furnace. The materials and structural forms of the heat insulation measures can be selected according to the actual heating temperature and heat insulation requirements.
[0062] In general, this application separates the side heating and top heating, and controls the temperature independently. Based on the ingot size and the difference in radial hydroxyl concentration, the required temperature difference is calculated using a formula, which precisely controls the temperature difference between the side and top hot zones of the quartz ingot. Ultimately, the optical uniformity and stress birefringence value of the quartz ingot are reduced to a very low level, meeting the optical application requirements with high stress birefringence requirements.
[0063] It should be understood that expressions such as "comprising" and "may include" as used in this application indicate the existence of the disclosed functions, operations, or constituent elements, and do not limit one or more additional functions, operations, and constituent elements. In this application, terms such as "comprising" and / or "having" may be interpreted as indicating a specific characteristic, number, operation, constituent element, component, or combination thereof, but should not be interpreted as excluding the existence or possibility of adding one or more other characteristics, numbers, operations, constituent elements, components, or combinations thereof.
[0064] It should be understood that the terms “center,” “upper,” “lower,” “front,” “rear,” “left,” “right,” “vertical,” “horizontal,” “inner,” “outer,” “clockwise,” “counterclockwise,” “axial,” “radial,” and “circumferential” indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this application.
[0065] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.
[0066] In this application, unless otherwise expressly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection between two components. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances.
[0067] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. An annealing method for quartz glass used in optical components, characterized in that, Includes the following steps: The cylindrical quartz glass to be annealed is placed in the annealing equipment, and the required temperature difference T is calculated based on the radial hydroxyl concentration difference and dimensional parameters of the quartz glass. The quartz glass is annealed independently in two separate temperature control zones, namely the circumferential side area and the top area. The circumferential side area and the top area are heated to the same temperature at the same time. Then, the top area is cooled down before the circumferential side area. During the cooling process, the temperature of the top area is kept lower than the temperature of the circumferential side area by a temperature difference T, thereby completing the annealing process of the quartz glass. The temperature difference T is determined using the following formula: T = T1 + T2; T1 = a × △OH; T2=b×(R 2 / 4c)×d; In the formula, T is the temperature difference, T1 is the temperature value that needs to be compensated for the difference in hydroxyl groups, T2 is the temperature value that needs to be compensated for the difference in size, a is the hydroxyl group influence base, ΔOH is the absolute value of the difference in radial hydroxyl concentration in the quartz glass, b is a constant, R is the radius of the quartz glass, c is the thermal diffusivity of the quartz glass at the center value of the first stage cooling range in the circumferential region of the side, and d is the cooling rate of the first stage in the circumferential region of the side.
2. The annealing method for quartz glass used in optical components according to claim 1, characterized in that, The annealing process of the circumferential area of the side of the quartz glass is as follows: first, heat to a first preset temperature t1 and hold for a first preset time s1, then cool to a second preset temperature t2 at a first preset cooling rate v1 and hold for a second preset time s2, and finally cool to a third preset temperature t3 at a second preset cooling rate v2, wherein the second preset cooling rate v2 is greater than the first preset cooling rate v1.
3. The annealing method for quartz glass used in optical components according to claim 2, characterized in that, The annealing process for the top region of the quartz glass is as follows: simultaneously heating the circumferential region of the side of the quartz glass to the first preset temperature t1 and holding it at that temperature for a third preset time s3, then cooling it down to the fourth preset temperature t4 at the first preset cooling rate v1 and holding it at that temperature for a fourth preset time s4, and finally cooling it down to the third preset temperature t3 at the second preset cooling rate v2.
4. The annealing method for quartz glass used in optical components according to claim 3, characterized in that, The first preset temperature t1 is 1260℃~1280℃, the first preset time s1 is 20h~50h, the first preset cooling rate v1 is 1℃ / h~10℃ / h, the second preset temperature t2 is 1050℃~1000℃, the second preset time s2 is 20h~50h, the second preset cooling rate v2 is 5℃ / h~30℃ / h, and the third preset temperature t3 is 500℃.
5. The annealing method for quartz glass used in optical components according to claim 3, characterized in that, The first preset time s1 and the third preset time s3 satisfy the following conditions: ; And / or, the second preset time s2 and the fourth preset time s4 satisfy the following conditions: 。 6. The annealing method for quartz glass used in optical components according to claim 3, characterized in that, The second preset temperature t2 and the fourth preset temperature t4 satisfy the following conditions: t2-t4=T.
7. The annealing method for quartz glass used in optical components according to claim 1, characterized in that, Thermal insulation measures are employed to reduce heat transfer between the circumferential side area and the top area.
Citation Information
Patent Citations
Annealing method of quartz glass
CN108383365A
High-uniformity high-hydroxyl quartz glass and preparation method thereof
CN120698691A